Vida Útil de las Celdas en el Complejo Ambiental del Cantón Santo Domingo de los Colorados, Ecuador - Mantuano, Marcel Oswaldo Méndez; Jiménez, Keyla Ximena Bodero; Robles, Darwin Vicente Apolo; Rosado, Ãngel Raúl Huayamave (European Scientific Journal, ESJ, 2019)
The new environmental trend isthe minimization of the impacts caused by solid waste. This is achieved through the formulation of public policies that are articulated to local actions, which allows the achievement of environmental, social, and financial sustainability in the 221 cantons of Ecuador. It focuses on the valuation of resources that are discarded and that have the potential to be reused or recycled. As a result, it is necessary that the municipalities should manage in an eco-friendly and eco-efficient manner their environmental liabilities (polluting waste generated by productive or economic activity), ensuring that these areas generate the least possible environmental impact. With this background, this paper focuses on analyzing the current situation of the Environmental Solid Waste Complex of the city of Santo Domingo de los Colorados, with emphasis on the area of the cells where the solid waste is deposited. The objective was to determine the useful life of the cells and analyze the main environmental liabilities generated by establishing introspectively the potential environmental impacts. It also aims to make an improvement proposal to achieve an effective articulation of Solid Waste Management. La nueva tendencia ambiental es la minimización de los impactos causados por los residuos sólidos, a través de la formulación de polÃticas públicas que sean articuladas a las acciones locales; que permitan lograr la sostenibilidad ambiental, social y financiera en los 221 cantones del Ecuador, enfocando a la valoración de los recursos que son desechados y que poseen la potencialidad para ser reutilizados o reciclados. Para ello, es necesario que los municipios administren de manera ecoamigable y ecoeficiente sus pasivos ambientales (residuos contaminantes generados por actividad productiva o económica), asegurando que dichas áreas generan el menor impacto ambiental posible. Con estos antecedentes, el presente trabajo analiza la situación actual del Complejo Ambiental de Residuos Sólidos de la ciudad de Santo Domingo de los Colorados, con énfasis en el área de las celdas donde se depositan los residuos sólidos. Se tuvo por objeto determinar la vida útil de las celdas; analizar los principales pasivos ambientales generados, estableciendo introspectivamente los potenciales impactos ambientales y realizar una propuesta de mejora para lograr una efectiva articulación de la Gestión de Residuos Sólidos.